2019
DOI: 10.1111/1471-0307.12630
|View full text |Cite
|
Sign up to set email alerts
|

Microbial, physico‐chemical and sensory characteristics of mango juice‐enriched probiotic dairy drinks

Abstract: This study aimed to determine whether mango juice can improve the viability of probiotics in a fermented dairy-based beverage whilst maintaining its quality characteristics. Formulations containing Lactobacillus acidophilus La-5 culture, whole cow's milk and varying concentrations of mango juice (0%, 10%, 20%, 30% and 40% (w/w)) were produced and stored for five weeks at 4°C. Results showed that probiotic viability was enhanced with the addition of 10% mango juice. Additionally, this formulation improved probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
3
33
0
3
Order By: Relevance
“…The samples were incubated at 37 °C. Aliquots of 1 mL were removed to assess resistance to gastric juices (after 1-, 60- and 180-min exposure) and to intestinal juices with or without 0.3% bile (after 1-, 60- and 240-min exposure) [ 10 ]. Serial dilutions and spread plating were then performed to determine total viable counts at each time points as described in Section 2.3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were incubated at 37 °C. Aliquots of 1 mL were removed to assess resistance to gastric juices (after 1-, 60- and 180-min exposure) and to intestinal juices with or without 0.3% bile (after 1-, 60- and 240-min exposure) [ 10 ]. Serial dilutions and spread plating were then performed to determine total viable counts at each time points as described in Section 2.3 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these products are becoming increasingly popular among health-conscious consumers. Fruit juices, legumes, cereals and dry fruits are increasingly used to fortify yogurt [ 8 , 9 , 10 ]. It is difficult to produce yogurt with a good consistency using only probiotic cultures, without starter cultures such as Lactobacillus delbrueckii subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Mituniewicz‐Małek et al () showed that the use of L. acidophilus in production of fermented goat milk had undesirable sensory properties, whereas the use of L. rhamnosus showed more desirable properties than B. lactis . Ryan et al () evaluated the properties of probiotic dairy drinks enriched with mango juice and fermented milk with L. acidophilus . The results of the study showed that the sensory properties were positively affected as the proportion of mango juice increased.…”
Section: Resultsmentioning
confidence: 99%
“…Fermantasyon süresi boyunca haftalık olarak örneklerin pH değeri Hanna (HI 2215, Almanya) pH metre ve briks (% çözünür kuru madde içeriği) el refraktometresi (Atago Refractometer N-1E, Japonya) kullanılarak Budak (2015)'te belirtildiği şekilde ölçülmüştür. Viskozite (50 ve 100 rpm) (Brookfield, Middleboro, MA, ABD) 2 numaralı spindle kullanılarak oda sıcaklığında (Ryan 2019), mantar ağırlığı hassas terazide (Radwag PS-1000 R2, Polonya), su aktivitesi (a w ) su aktivitesi ölçüm cihazında (Novasina, LabTouch, İsviçre), renk değerleri ise kolorimetre (Konika Minolta Krom Metre CR-400) kullanılarak Akarca ve ark. (2015)'e göre ölçülmüştür.…”
Section: Fiziksel Ve Kimyasal Analizlerunclassified